Joyce Carol Oates, the writer who runs: notes on the creative process - Amabile, Luís Roberto (Manuscrítica: Revista de Crítica Genética, 2014)
Joyce Carol Oates has been one of the most prolific authors in the last five decades. Since her debut in 1963, the American writer wrote 140 books, including novels, collections of short stories, children’s and juvenile fiction, poems and plays. She also has won some of the most important literary prizes in the USA. This article aims to establish connections between the ideas of Joyce Carol Oates on literary creation and the reflections of some intellectuals about the subject. Oates’ ideas are taken from her interview for The Paris Review. Her answers are compared with statements taken from texts by Roland Barthes, Maurice Blanchot, Jean-Paul Sartre, Alberto Manguel, John Gardner and Philippe Willemart.